How sphingolipids affect T cells in the resolution of inflammation - Hartel, Jennifer Christina; Merz, Nadine; Grösch, Sabine (Frontiers in Pharmacology, 2022)
The concept of proper resolution of inflammation rather than counteracting it, gained a lot of attention in the past few years. Re-assembly of tissue and cell homeostasis as well as establishment of adaptive immunity after inflammatory processes are the key events of resolution. Neutrophiles and macrophages are well described as promotors of resolution, but the role of T cells is poorly reviewed. It is also broadly known that sphingolipids and their imbalance influence membrane fluidity and cell signalling pathways resulting in inflammation associated diseases like inflammatory bowel disease (IBD), atherosclerosis or diabetes. In this review we highlight the role of sphingolipids in T cells in the context of resolution of inflammation to create an insight into new possible therapeutical approaches.